Multimodal Behavior Program for ADHD Incorporating Yoga and Implemented by High School Volunteers: A Pilot Study. (11th August 2011) - Mehta, Sanjiv; Mehta, Vijay; Mehta, Sagar; Shah, Devesh; Motiwala, Ashok; Vardhan, Jay; Mehta, Naina; Mehta, Devendra
Abstract : A low-cost resource approach to ADHD therapy would be a practical approach to treating children in developing countries. Research has shown that ADHD is prevalent in all areas of the world, and yet treatment for children in more impoverished countries is still lacking. The approach taken was to combine yoga and meditation combined with multimodal behavioral therapy program for children ageing 6 to 11. The program was kept low cost by using trained high school volunteers and integrating the program within the public school. After 6 weeks of the program, 90.5% of children showed improvement as measured by their performance impairment score, a measurement of academic performance. Parent and Teacher evaluations of behavior also found improvement as 25 of the 64 children (39.1%) improved into the normal range as measured by the Vanderbilt questionnaire. Moreover, children could successfully learn both yoga and meditation from high school students irrespective of their age, ADHD type, or initial performance impairment. The results demonstrate efficacy of a multimodal behavioral program incorporating yoga and meditation. The use of high school volunteers from schools in the area demonstrates an effective low-cost and universally applicable approach.